Mint Oil, ɤ-Tocopherol, and Whole Yeast Cell in Sow Diets Enhance Offspring Performance in the Postweaning Period - Hernandez, Lily P.; Dunn, James L.; Wenninghoff, Joel; Hesse, Amanda; Levesque, Crystal L. (Frontiers in Veterinary Science, 2021)
Times of high metabolic activity in gestation and lactation, as well as periods of stress at weaning, can lead to greater incidences of oxidative stress in the dam and offspring during the suckling and postweaning period. Oxidative stress is an imbalance between prooxidant molecules and the antioxidant defense system that can negatively impact growth and/or reproductive performance. The objective of this research was to evaluate the effectiveness of whole yeast cell, peppermint oil, and ɤ-tocopherol in gestation and lactation on maternal oxidative status and offspring growth from birth to market. In study 1, 45 sows and gilts were assigned to one of four diets [control diet (CON), control + whole yeast cell (YC), control + mint oil top dress (MO), and control + yeast cell and mint oil top dress (YCMO)] provided from d110 of gestation through to weaning. A total of 481 weaned offspring were randomly allotted to pens balanced by weight and litter within maternal treatment and received the same dietary treatment as the sow for 35 days postwean in a four-phase feeding regimen. In study 2, 53 sows and gilts were allotted to four diet regimens similar to study 1 [CON, YC, MO, and control + ɤ-tocopherol (GT)] from d5 postbreeding to weaning. At weaning, 605 piglets were randomly allotted to pens, balanced by weight and litter within maternal treatment and fed a common diet for 126 days postwean in a nine-phase feeding regimen. Maternal dietary treatment did not impact sow body weight, piglet birth weight, and litter size in either study. In study 1, piglets from YC sows were heavier (p < 0.05) at weaning than CON animals. In the postwean period, overall daily gain was greater (p < 0.05) for CON-fed pigs than YCMO pigs, with overall feed intake greater (p < 0.05) for YCMO- than MO-fed pigs, resulting in lower (p < 0.05) Gain to Feed (G:F) in YCMO-fed pigs. In study 1, glutathione content in milk tended to be lower (p < 0.10) in MO than in YCMO sows. In study 2, piglets from GT-fed sows tended to be heavier (p < 0.10) at weaning than YC piglets. Lightweight pigs from CON sows tended to be lighter (p < 0.10) than pigs from all other treatment groups at weaning and day (d) 29 postwean. Lightweight MO and GT pigs were heavier at d42 (p < 0.05) than CON and YC pigs. At d70 postwean, GT pigs tended to be heavier than CON pigs. Lightweight MO pigs had greater gain (p < 0.05) during the finishing period than all other treatment groups. With respect to sow oxidative status in study 2, glutathione content in colostrum and d4 and 14 milk samples did not differ by maternal treatment. Superoxide dismutase activity in sow sera, colostrum, and milk did not differ between diets in either study. Whole yeast cell and ɤ-tocopherol supplementation in sow lactation diets resulted in heavier offspring. However, pre- and postnatal exposure to mint oil benefited lightweight pigs up to market weight.